2015
DOI: 10.5993/ajhb.39.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Risk Assessment of Adolescents' Electronic Cigarette Perceptions

Abstract: Objectives Adapt an established instrument for measuring adolescents’ cigarette-related perceptions for new application with electronic cigarettes (e-cigarettes). Methods In this exploratory study, 104 male high school students (40% tobacco ever-users) estimated the probability of potential e-cigarette risks (eg, lung cancer) or benefits (eg, look cool). We calculated associations between risk/benefit composite scores, ever-use, and use intention for e-cigarettes and analogously for combustible cigarettes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 30 publications
3
67
1
1
Order By: Relevance
“…4,6,9 For example, our findings are consistent with those of Ambrose et al 4 who found that ever use of e-cigarettes was significantly associated with perceiving e-cigarettes as less harmful than cigarettes among middle and high school students nationwide. Amrock et al 6 also investigated the comparative harm of e-cigarettes to cigarettes, and found that both ever users and current users of e-cigarettes reported that e-cigarettes were less harmful than cigarettes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…4,6,9 For example, our findings are consistent with those of Ambrose et al 4 who found that ever use of e-cigarettes was significantly associated with perceiving e-cigarettes as less harmful than cigarettes among middle and high school students nationwide. Amrock et al 6 also investigated the comparative harm of e-cigarettes to cigarettes, and found that both ever users and current users of e-cigarettes reported that e-cigarettes were less harmful than cigarettes.…”
Section: Discussionsupporting
confidence: 91%
“…Amrock et al 6 also investigated the comparative harm of e-cigarettes to cigarettes, and found that both ever users and current users of e-cigarettes reported that e-cigarettes were less harmful than cigarettes. Chaffee et al 9 examined perceived risks and benefits of e-cigarettes in a sample of high school boys and found that increasing perceived risk was associated with lower prevalence of ever use of e-cigarettes. Our study extends these findings further, as it is specific to the absolute harm and addictiveness associated with e-cigarettes – not compared to other product use, like cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There also exists a strong observable relationship between perceptions of tobacco-related risks and benefits and adolescents’ initiation and continued tobacco use [1316]. Adolescents with smoking experiences have higher perceptions of benefits and lower perceptions of risks compared to adolescents who have never smoked [4].…”
mentioning
confidence: 99%